From library to learning center: Reading transformation within the era of information in terms of spaces - Umut Tuğlu Karslı (Nilay ÖZSAVAŞ ULUÇAY, 2021)
In the era of information parallel to technological developments, the methods and tools used to access information have been transformed and the functions of the libraries have diversified and transformed in line with the needs of information workers. Parallel to these changing requirements, library spaces have turned into activity-based “learning centers” that are visited for creating and sharing new information, rather than being places where merely books are physically stored, borrowed and read. The aim of this study is to examine the transformation observed in library spaces depending on the social, cultural and technological developments within the era of information and to reveal the spatial characteristics that incline their interior designs. In this context, the changing learning and working practices of information societies have been primarily examined; the transformation in library functions is revealed and the spatial characteristics that direct the interior design of new libraries are investigated. In this study, as a method, a literature review was carried out, prominent spatial characteristics were systematically reclassified and explained with the help of best practice library cases. As a result, the spatial characteristics of new libraries have been determined as “building community/social permeability”, “diversity”, “interactivity”, “conformity to information technologies” and “design aesthetics/atmosphere”.